The predictive effects of motivation toward science on TIMSS grade 8 students’ science achievement: a comparative study between Malaysia and Singapore - Lay, Yoon Fah; A.L. Chandrasegaran (2016)
Background: TIMSS routinely presents very powerful evidence showing that within countries students with more positive motivation toward science have substantially higher achievement. The results from TIMSS 2011 are consistent with previous assessments. This study explored the predictive effects of motivation toward science on science achievement among Malaysian and Singaporean eighth graders who participated in the TIMSS 2011.